Low-Dose Radiation Therapy for COVID-19: Promises and Pitfalls. Issue 1 (19th November 2020) - Venkatesulu, Bhanu P; Lester, Scott; Hsieh, Cheng-En; Verma, Vivek; Sharon, Elad; Ahmed, Mansoor; Krishnan, Sunil
Abstract: The coronavirus disease-2019 (COVID-19) pandemic caused by SARS-CoV-2 has exacted an enormous toll on healthcare systems worldwide. The cytokine storm that follows pulmonary infection is causally linked to respiratory compromise and mortality in the majority of patients. The sparsity of viable treatment options for this viral infection and the sequelae of pulmonary complications have fueled the quest for new therapeutic considerations. One such option, the long-forgotten idea of using low-dose radiation therapy, has recently found renewed interest in many academic centers. We outline the scientific and logistical rationale for consideration of this option and the mechanistic underpinnings of any potential therapeutic value, particularly as viewed from an immunological perspective. We also discuss the preliminary and/or published results of prospective trials examining low-dose radiation therapy for COVID-19.